How do Car Owners Familiarize and Adapt to Unfamiliar Vehicle Technologies? - Vibeke M Uhlving; Alena Høye; Kjell Vegard Weyde (Findings)
Many drivers lack relevant knowledge about advanced driver assistance systems (ADAS), and how they learn about ADAS is mainly haphazard. We conducted interviews with six experts from the automobile industry and eight drivers. Few drivers actively engage with ADAS features and settings in their vehicles and many fail to check or familiarize themselves with ADAS in an unfamiliar car. Moreover, the research highlights that it is not rare for drivers to misinterpret typical ADAS responses as technical issues.